Shear behavior of fiber-reinforced ultra-high performance concrete beams. (1st August 2018) - Mészöly, Tamás; Randl, Norbert
Graphical abstract: Highlights: 20 single span beams made of ultra-high performance concrete were tested in shear. Main parameters were the steel fiber content and the degree of shear reinforcement. The cracking process was monitored by a digital image correlation system. The impact of fibers on cracking, stiffness and shear resistance is significant. The fiber effect in shear correlates with the post-peak uniaxial tensile strength. Abstract: Twenty I-shaped beams made of ultra-high performance concrete (UHPC) with different steel fiber content (up to 2% by volume) and with varying degrees of shear reinforcement (no stirrups or with diameter 10 mm stirrup, 125–300 mm spacing) were tested in shear. The mean compressive strength of the concrete was around 170 MPa. All tests failed in shear. The study investigated the effect of the traditional transverse shear reinforcement and the effect of the fiber reinforcement on the shear behavior as well as the interaction of both parameters, considering the failure mechanisms and the shear capacity. The cracking process was monitored by a digital image correlation (DIC) measurement system and the results of the evaluation are presented. The measured ultimate shear capacity of the different setups was compared to the current AFGC design approach.